1990
DOI: 10.1007/bf01310504
|View full text |Cite
|
Sign up to set email alerts
|

A structural model for the genome of echovirus 22

Abstract: We have proposed previously that the structural model for the echovirus 22 genome is a single-stranded RNA molecule that has folded back upon itself to form a stable "hairpin" at the 5'-terminus. The vRNA of echovirus 22 has been characterized further by digestion with selective ribonucleases, electrophoresis in composite gels, hydrodynamic studies in density gradients of Cs2SO4 and sucrose, thermal denaturation and 3'-terminal ribonucleotide analysis. Based on these observations, the genome of echovirus 22 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…At the antigenic level, EV22 appears enteroviruslike: EV22 proteins share an enteroviral group-specific antigen recognized by enterovirus-immune T cells which is not shared by the cardioviruses. Determinations of the S value for denatured EV22 RNA and the density in CsCl are consistent with enteroviral biophysical characteristics (2,16). However, EV22 also shares several important biological characteristics with the cardioviruses (2).…”
supporting
confidence: 61%
See 1 more Smart Citation
“…At the antigenic level, EV22 appears enteroviruslike: EV22 proteins share an enteroviral group-specific antigen recognized by enterovirus-immune T cells which is not shared by the cardioviruses. Determinations of the S value for denatured EV22 RNA and the density in CsCl are consistent with enteroviral biophysical characteristics (2,16). However, EV22 also shares several important biological characteristics with the cardioviruses (2).…”
supporting
confidence: 61%
“…EV22 fails to shut off host cell protein synthesis efficiently in infected cells and acts as an efficient message in rabbit reticulocyte lysate in vitro translation systems (2). Other studies have demonstrated evidence for the presence of an extensive 5' hairpin structure in the viral RNA (16,17). Limited sequence data suggest the 3' end of the genome is significantly diverged from other enteroviral sequences and may as well form a hairpin structure (1).…”
mentioning
confidence: 99%
“…Distinctive cytopathogenicity compared to other viruses in the enterovirus group (disappearance of the nucleolus and nuclear chromatin) was also reported on the basis of light and electron microscopy studies of cells infected with HPEV1 and HPEV2 (27,56,61). Evidence of exceptional secondary structure in the HPEV1 genome compared to poliovirus RNA was reported later (53,54). Another difference from typical enteroviruses was the apparent lack of host cell protein synthesis shutoff (7,58).…”
Section: Isolation and Primary Characterization Of Hpev1 And Hpev2mentioning
confidence: 86%